The glass wall : lives on the Baltic frontier - Egremont, Max, 1948- (New York : Picador, 2021)
"Max Egremont, author of Some Desperate Glory, tells stories from the 'Glass Wall' between Europe and Asia"--
"Originally published in 2021 by Picador, Great Britain."
Includes bibliographical references and index.
Keywords: Egremont, Max, -- 1948- -- Travel -- Baltic States; Germans -- Baltic States -- History; Russians -- Baltic States -- History; Baltic States -- History; Baltic States -- History -- German occupation, 1941-1944.; Baltic States -- History -- Soviet occupation, 1939-1941.